Examination of the Residency Interview Process for Academic Pathology Departments - Candice C. Black DO (Elsevier, 2016)
Annual resident recruitment is a complex undertaking that requires many departmental resources of faculty time and effort and in many cases financial investment for meals and lodging. The applicants represent the future of the profession as well as the providers of patient care in the respective training programs. Although we understand the importance of this process, as we become more and more distracted by financial, administrative, and academic duties, the demands of recruitment have not decreased and continue annually. In an attempt to find the best practices for the improvement in our methods of recruitment, a review of the literature on the employment interviews with a specific eye to pathology residency relevant information was conducted. This article reviews some of the factors proven to be important to the applicants as well as an examination of the structure of the interview and the postinterview applicant evaluation process.